The Fifth Semester Students’ Competence in Distinguishing English Derivation and Inflection - Sofyan, Nurlaily; Latrisi, Waega; Umasugi, Faujia (EDU Journal - English Department of UMMU Journal, 2023)
Abstract: This research aims "to know the extent of students' competence in distinguishing English derivation and inflection." This study used a qualitative descriptive method. The researchers applied a test sheet as an instrument. The first step is for the researcher to give multiple-choice test sheets and collect the students' test results. Then, proceed with interviews that are answered directly by students. The total respondents were 17 active students. This research took place at the Muhammadiyah University of North Maluku, Faculty of Education, majoring in English, especially for the semester students. Based on the data presented in this study, the researchers concluded that the competence of students in differentiating derivation and inflection through multiple choice test sheets was still unsatisfactory because from the beginning to the end, the researchers found many students who had minimal competence, so most of them answered the questions given by researchers is not good, then the total average score obtained from the derivation and inflection is mean 48 which is in the poor category. The results of this study may indicate that most students are still challenged to distinguish English derivation and inflection well.